Progress Towards a National Cardiac Procedure Database-Development of the Australasian Society of Cardiac and Thoracic Surgeons (ASCTS) and Melbourne Interventional Group (MIG) Registries - Chan, W.; Clark, D.; Ajani, A.; Yap, C.; Andrianopoulos, N.; Brennan, A.; Dinh, D.; Shardey, G.; Smith, J.; Reid, Christopher; Duffy, S. (2011)
Since the call for a National Cardiac Procedures Database in 2001, much work has been accomplished in both cardiac surgery and interventional cardiology in an attempt to establish a unified, systematic approach to data collection, defining a common minimum dataset pertinent to the Australian context, and instituting quality control measures to ensure integrity and privacy of data. In this paper we outline the aims of the Australasian Society of Cardiac and Thoracic Surgeons (ASCTS) and the Melbourne Interventional Group (MIG) registries, and propose a comprehensive set of standardised data elements and their definitions to facilitate transparency in data collection, consistency between these and other data sets, and encourage ongoing peer-review. The aims are to improve outcomes for patients by determining key performance indicators and standards of performance for hospital units, to allow estimation of procedural risks and likelihood of outcomes for patients, and to report outcomes to relevant stake-holders and the public. © 2010 Australasian Society of Cardiac and Thoracic Surgeons and the Cardiac Society of Australia and New Zealand.